Differential impacts of ocean acidification and warming on winter and summer progeny of a coastal squid (Loligo vulgaris) - Rosa, Rui (2018)
Little is known about the capacity of early life stages to undergo hypercapnic and thermal acclimation under the future scenarios of ocean acidification and warming. Here, we investigated a comprehensive set of biological responses to these climate change-related variables (2°C above winter and summer average spawning temperatures and ΔpH=0.5 units) during the early ontogeny of the squid Loligo vulgaris. Embryo survival rates ranged from 92% to 96% under present-day temperature (13-17°C) and pH (8.0) scenarios. Yet, ocean acidification (pH 7.5) and summer warming (19°C) led to a significant drop in the survival rates of summer embryos (47%, P<0.05). The embryonic period was shortened by increasing temperature in both pH treatments (P<0.05). Embryo growth rates increased significantly with temperature under present-day scenarios, but there was a significant trend reversal under future summer warming conditions (P<0.05). Besides pronounced premature hatching, a higher percentage of abnormalities was found in summer embryos exposed to future warming and lower pH (P<0.05). Under the hypercapnic scenario, oxygen consumption rates decreased significantly in late embryos and newly hatched paralarvae, especially in the summer period (P<0.05). Concomitantly, there was a significant enhancement of the heat shock response (HSP70/HSC70) with warming in both pH treatments and developmental stages. Upper thermal tolerance limits were positively influenced by acclimation temperature, and such thresholds were significantly higher in late embryos than in hatchlings under present-day conditions (P<0.05). In contrast, the upper thermal tolerance limits under hypercapnia were higher in hatchlings than in embryos. Thus, we show that the stressful abiotic conditions inside the embryo's capsules will be exacerbated under near-future ocean acidification and summer warming scenarios. The occurrence of prolonged embryogenesis along with lowered thermal tolerance limits under such conditions is expected to negatively affect the survival success of squid early life stages during the summer spawning period, but not winter spawning.